Treatment of chronic lymphocytic leukemia with bendamustine in an HIV‐infected patient on antiretroviral therapy: a case report and review of the literature. Issue 6 (22nd April 2015) - Shimada, Naoki; Yuji, Koichiro; Ohno, Nobuhiro; Koibuchi, Tomohiko; Oyaizu, Naoki; Uchimaru, Kaoru; Tojo, Arinobu
Key Clinical Message Few reports have described the coincidence of chronic lymphocytic leukemia (CLL) and HIV. We administered bendamustine to an HIV‐positive refractory CLL patient and obtained a significant objective response. Our results indicate that bendamustine can be used in HIV‐infected CLL patients. We also reviewed 12 cases of CLL with HIV infection.